The effect of unburned gas axial velocity on the characteristics of rotational flame during flashback - Bufares, Ahmed M. (American Institute of Physics, 2012)
The qualitative study has been carried out to investigate the effect of axial velocity of unburned gases on the flame characteristics during flame flashback in rotating burner. Our focus of study mainly on the flame shape and its behavior during flashback. It is found that the flame shape has been affected by the unburned gases axial velocity. Two flame shapes have been noticed the plate shape with cusp flame "fish flame" and upset dome flame. The cases that have been studied are flames at rotating speed 1200 rpm and 1620 rpm and several unburned gases axial velocity. Double concentric Bunsen rotating burner has been used in the study.